2019
DOI: 10.1002/fsn3.818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorogenic acid, epicatechin gallate, and quercetin on mucin expression and secretion in the Caco‐2/HT29‐MTX cell model

Abstract: Mucins are a family of large glycoproteins that represent the major structural components of the mucus and are encoded by 20 different mucin genes. Mucin expression can be modulated by different stimuli. In this study, we analyzed four mucins (MUC2, MUC3, MUC13, and MUC17) in coculture of Caco‐2/HT29‐MTX cells to demonstrate the variation in gene expression in the presence of antioxidant compounds like chlorogenic acid, epicatechin gallate, and quercetin (apple, tea, and coffee polyphenols, respectively). cocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In this study, we established an in vitro co-culture model of these two cell lines. This is in agreement with other studies using Caco-2 cells in combination with other cell lines (such as HT-29, HT-29-MTX and LS174T) in co-culture models to simulate the human intestinal epithelial layer 26 28 . The co-cultures were established on 2D Transwell inserts to mechanistically investigate the interaction of hypoxia and HS challenges on intestinal epithelium as measured by intestinal barrier function, heat shock response and oxidative stress response.…”
Section: Introductionsupporting
confidence: 92%
“…In this study, we established an in vitro co-culture model of these two cell lines. This is in agreement with other studies using Caco-2 cells in combination with other cell lines (such as HT-29, HT-29-MTX and LS174T) in co-culture models to simulate the human intestinal epithelial layer 26 28 . The co-cultures were established on 2D Transwell inserts to mechanistically investigate the interaction of hypoxia and HS challenges on intestinal epithelium as measured by intestinal barrier function, heat shock response and oxidative stress response.…”
Section: Introductionsupporting
confidence: 92%
“…Several studies have focused on understanding how individual phenolic compounds and some dietary extracts impact intestinal barrier function, but there is limited information on cereal phenolic extracts [ 22 , 78 , 79 , 80 ]. Intestinal barrier function can be conserved by the alleviation of oxidative stress and inflammation, induction of mucus production and reduction of intestinal permeability.…”
Section: Impact Of Polyphenols On Intestinal Barrier Functionmentioning
confidence: 99%
“…In vitro cell culture models are often used to simulate oxidative stress- and inflammation-induced damage in the intestines through the use of oxidants (such as hydrogen peroxide and oxysterols, cholesterol auto-oxidation products) and pro-inflammatory mediators such as interleukin 1 beta (IL-1β), tumour necrosis factor-α (TNF-α) or lipopolysaccharides (LPS), respectively [ 22 , 81 ]. Upon exposure to polyphenols, the protective response of the intestines may include the secretion of mucus (mucin proteins secreted by goblet cells to provide a physical barrier) and reduced intestinal permeability indicated by the expression of tight junction proteins ( Figure 2 ) [ 80 , 81 ]. Tight junction proteins such as occludin, zona occludens and other adhesion complexes seal adjacent cells to regulate permeability and maintain barrier integrity [ 82 ].…”
Section: Impact Of Polyphenols On Intestinal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the activation of the AMPK pathway via Trx‐1 regulates increased mucus production and may have a protective effect against diabetes. Recently, it was demonstrated that natural and dietary compounds (e.g., sulforaphane, bakuchiol, and arabinoxylan) exhibit protective effects against diet‐induced metabolic syndrome and diabetes as well as modify the secretion and composition of mucins associated with goblet cells (Li et al., 2019 ; Tian et al., 2021 ; Volstatova et al., 2019 ; Xin et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%